2007
DOI: 10.1111/j.1524-4741.2007.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Rare Species of Actinomyces as Causative Pathogens in Breast Abscess

Abstract: Actinomyces species are commensal flora usually found in the oropharynx, gastrointestinal tract, and female genital tract. Primary actinomycosis of the breast is an unusual condition, where the most commonly isolated pathogen has been Actinomyces israelii. In recent years, other Actinomyces strains have been found associated with breast disease. We present the first reported cases of breast infection caused by the rare species, Actinomyces turicensis and Actinomyces radingae. Both infections displayed chronici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 12 publications
2
23
0
1
Order By: Relevance
“…that have a predilection for causing invasive infections at specific body sites (2). Our study confirmed previous reports of the association of A. graevenitzii with pulmonary infections (33,34) and of A. radingae with SSTA infections of the upper body associated with chest or breast abscesses (35). In our study, we found that A. odontolyticus was the most common and diverse cause of invasive actinomycosis, including intraabdominal abscesses, osteomyelitis, pulmonary infections, and sepsis.…”
Section: Discussionsupporting
confidence: 81%
“…that have a predilection for causing invasive infections at specific body sites (2). Our study confirmed previous reports of the association of A. graevenitzii with pulmonary infections (33,34) and of A. radingae with SSTA infections of the upper body associated with chest or breast abscesses (35). In our study, we found that A. odontolyticus was the most common and diverse cause of invasive actinomycosis, including intraabdominal abscesses, osteomyelitis, pulmonary infections, and sepsis.…”
Section: Discussionsupporting
confidence: 81%
“…The first case report of an A. radingae breast infection (in a male patient that also lived in The Netherlands) was described by Attar et al in 2007 [2].…”
Section: Discussionmentioning
confidence: 99%
“…The most common isolated pathogen in breast actinomycosis is A. israelii. More recently, breast infections due to A. viscosus, A. turicensis, A. europaeus, A. odontolyticus, A. neuii and A. radingae have been described [2,3,9,10]. Breast actinomycosis may either present as a sinus tract, or with mass-like features mimicking malignancy, or may mimic mastitis.…”
Section: J Microbiol Infect Dis Wwwjmidonlineorg Vol 6 No 2 June mentioning
confidence: 99%
“…There was no clearly predominant Actinomyces species. Five cases reported coinfecting anaerobes (17,24), and one case reported coinfecting Staphylococcus aureus (20), with no mention of coinfecting organisms in 11 of 17 cases. Seven cases were recurrent infections, and a range of different treatment combinations were required to reach abscess resolution.…”
Section: Lothian Casesmentioning
confidence: 99%
“…This ranged from 2 to 3 weeks of oral antibiotics to incision and drainage with prolonged antibiotics for 2 to 6 months; the most extreme treatment was tumorectomy of the breast (22). As with our cohort of patients, prior to the diagnosis of Actinomyces breast infection, some patients had been repeatedly treated without success (14,17,20).…”
Section: Lothian Casesmentioning
confidence: 99%